Angiopoietin-2 silence alleviates lipopolysaccharide-induced inflammation, barrier dysfunction and endoplasmic reticulum stress of intestinal epithelial cells by blocking Notch signaling pathway. Issue 1 (1st January 2021) - Dai, Liying; Jie, Shuangshuang; Bi, Shaohua; Qing, Qing; Chen, Jun; Le Wang,
ABSTRACT: Necrotizing enterocolitis, a devastating gastrointestinal disease with high mortality, poses great threats to global health. Therefore, we conducted this study to explore the role of ANGPT2, as well as the potential mechanism, in necrotizing enterocolitis. IEC-6 cells were stimulated with lipopolysaccharide (LPS) to induce necrotizing enterocolitis model in vitro. The expression of ANGPT2 was measured by RT-qPCR. The cell viability was detected using CCK-8. Besides, the expressions of endoplasmic reticulum (ER) stress-related proteins, Notch signaling pathway-related proteins and tight junction proteins were checked by western blot. The apoptosis and inflammatory response were detected by TUNEL and ELISA, respectively. Moreover, with the adoption of TEER, the cell monolayer permeability was detected. The results showed that ANGPT2 expression was greatly increased after LPS induction. In addition, ANGPT2 knockdown significantly decreased the apoptosis, inflammatory response, barrier dysfunction and endoplasmic reticulum stress of LPS-induced IEC-6 cells. What is more, ANGPT2 knockdown could block Notch signaling pathway. Additionally, with the treatment of Jagged-1, the protective effect of ANGPT2 knockdown on LPS-induced intestinal injury was partly abolished. To sum up, silencing ANGPT2 could improve LPS-induced inflammation, barrier dysfunction and ER stress of intestinal epithelial cells via blocking Notch signaling pathway.